2022
DOI: 10.5209/rced.76370
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Emotional Intelligence and Burnout in non-formal teachers of people with disabilities

Abstract: INTRODUCTION. The direct involvement of professionals who carry out their activity with people with Intellectual Disability can generate a high degree of stress and emotional exhaustion. The objective of this research was to evaluate the relationship between emotional intelligence and dispositional optimism in processes of professional Burnout. METHOD. One hundred forty-four subjects participated in this study, belonging to the Andalusian Association of Organizations in favor of people with Intellectual Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The positive effects of EI and adaptive response or resilience, related to life satisfaction, may promote effective coping strategies in adverse situations [40,41]. If we combine the analysis of these variables, it has been shown that people with high EI scores are more satisfied with life [40,42,43]. Although the positive influence of EI on life satisfaction has been reported in different studies, the enhancing effect on resilience has not been considered [41,44,45].…”
Section: Effect Of Emotional Intelligence On Resilience and Life Sati...mentioning
confidence: 99%
“…The positive effects of EI and adaptive response or resilience, related to life satisfaction, may promote effective coping strategies in adverse situations [40,41]. If we combine the analysis of these variables, it has been shown that people with high EI scores are more satisfied with life [40,42,43]. Although the positive influence of EI on life satisfaction has been reported in different studies, the enhancing effect on resilience has not been considered [41,44,45].…”
Section: Effect Of Emotional Intelligence On Resilience and Life Sati...mentioning
confidence: 99%